Mesenchymal stem/stromal cells genetically engineered to produce vascular endothelial growth factor for revascularization in wound healing and ischemic conditions. (1st November 2018) - Fierro, Fernando A.; Magner, Nataly; Beegle, Julie; Dahlenburg, Heather; Logan White, Jeannine; Zhou, Ping; Pepper, Karen; Fury, Brian; Coleal‐Bergum, Dane Philip; Bauer, Gerhard; Gruenloh, William; Annett, Geralyn; et al.
Abstract : Mesenchymal stem/stromal cells (MSCs) may be able to improve ischemic conditions as they can actively seek out areas of low oxygen and secrete proangiogenic factors. In more severe trauma and chronic cases, however, cells alone may not be enough. Therefore, we have combined the stem cell and angiogenic factor approaches to make a more potent therapy. We developed an engineered stem cell therapy product designed to treat critical limb ischemia that could also be used in trauma‐induced scarring and fibrosis where additional collateral blood flow is needed following damage to and blockage of the primary vessels. We used MSCs from normal human donor marrow and engineered them to produce high levels of the angiogenic factor vascular endothelial growth factor (VEGF). The MSC/VEGF product has been successfully developed and characterized using good manufacturing practice (GMP)‐compliant methods, and we have completed experiments showing that MSC/VEGF significantly increased blood flow in the ischemic limb of immune deficient mice, compared to the saline controls in each study. We also performed safety studies demonstrating that the injected product does not cause harm and that the cells remain around the injection site for more than 1 month after hypoxic preconditioning. An on‐demand formulation system for delivery of the product to clinical sites that lack cell processing facilities is in development.